KELEMBAGAAN WILAYAT AL-HISBAH DALAM KONTEKS PENERAPAN SYARIAT ISLAM DI PROVINSI ACEH - Muhibbuthabry, Muhibbuthabry (SCAD Independent, 2014)
Province of Aceh is the only province in the region of the Republic of Indonesia (Republic of Indonesia) after the New Order which granted legal protection to apply Islamic law in many aspects of life. The provision is based on Law No. 44 Year 1999 on Implementation Features Special Province of Aceh. To oversee the implementation of Islamic law, then set up an institution of Wilayat al-hisbah. The institute is part of the implementation aspects of Islamic law in Aceh province are still warm and discussed intensively by many. Wilayat al-hisbah has strong roots in the process of implementing Sharia in the middle of the lives of Muslims. The institute serves as an authorized agency and authority to control and supervise the implementation of the law in the midst of people's lives in the jurisdiction of Aceh province. However, on the other hand still raises many problems. The issue includes conceptual issues and legal theories adopted and application problems. This essay tries to discuss about Wilayat al-hisbah institutions in the context of the application of Islamic law in Aceh province, given that law enforcement is an integral part of the vision and mission of the Muslim community life in this area.